MMP20 Active-site Mutation in Hypomaturation Amelogenesis Imperfecta - Ozdemir, D. (2005)
The Amelogenesis Imperfecta (AI) are a group of clinically and genetically heterogeneous disorders that affect enamel formation. To date, mutations in 4 genes have been reported in various types of AI. Mutations in the genes encoding the 2 enamel proteases, matrix metalloproteinase 20 (MMP20) and kallikrein 4 (KLK4), have each been reported in a single family segregating autosomal-recessive hypomaturation AI. To determine the frequency of mutations in these genes, we analyzed 15 Turkish probands with autosomal-recessive hypo-maturation AI for MMP20 and KLK4 gene mutations. No KLK4 mutations were found. A novel MMP20 mutation (g.16250T>A) was found in one family. This missense mutation changed the conserved active-site His226 residue of the zinc catalytic domain to Gln (p.H226Q). Zymogram analysis demonstrated that this missense mutation abolished MMP20 proteolytic activity. No MMP20 mutations were found in the remaining 14 probands, underscoring the genetic heterogeneity of hypomaturation AI.